2021
DOI: 10.1108/ci-08-2020-0139
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for the identification of competent project managers for construction projects in Nepal

Abstract: Purpose Project manager’s competency is crucial in the construction sector for the successful completion of projects, particularly in the case of developing countries like Nepal. Therefore, it is very essential to select competent project managers by finding the competency factors required by them. Hence, this study aims to identify the characteristics of competent project managers by expert opinion method and to evaluate their competency level by a questionnaire survey to develop a prediction model using a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…In this study, two competence gaps were identified in the PMCDF guide, they are: Information Technology Skills and Analytical Thinking [64]. For Karki and Hadikusumo [65] and Pereira and Freitas [64], Analytical Thinking is the ability to develop an understanding of a situation or problem, dividing it into smaller parts to trace the cause and implications of the situation or problem.…”
Section: Project Type -Remote Teamsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, two competence gaps were identified in the PMCDF guide, they are: Information Technology Skills and Analytical Thinking [64]. For Karki and Hadikusumo [65] and Pereira and Freitas [64], Analytical Thinking is the ability to develop an understanding of a situation or problem, dividing it into smaller parts to trace the cause and implications of the situation or problem.…”
Section: Project Type -Remote Teamsmentioning
confidence: 99%
“…[100]- [101]; Environmental Legislation and Administration [12], [77]; Continuous Improvement [49], [77], [92], [94]; Agile Mindset [31], [70]; Multiple Project Management [38]; Analytical Thinking [16], [32], [55], [65], [70]; Critical Thinking [55], [94], [104]; Strategic Thinking [70], [71], [77], [81], [90]; Self-Taught [88], [94]; [Strategic Planning [91].…”
Section: Project Type -Construction Industrymentioning
confidence: 99%
See 3 more Smart Citations